2021
DOI: 10.1002/jbt.22854
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and evaluation of curcumin‐loaded endodontic reparative material

Abstract: Curcumin (CUR) is an ancient therapeutic agent with remarkable antimicrobial and antiinflammatory properties. The purpose of the current study was to synthesize and evaluate a curcumin-based reparative endodontic material to reduce infection and inflammation besides the induction of mineralization during the healing of the dentin-pulp complex.Poly-ɛ-caprolactone (PCL)/gelatin (Gel)/CUR scaffold was synthesized and assessed by scanning electron microscopy, Fourier transform infrared spectroscopy, and thermograv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Hesperetin is known for its anti-inflammatory and antioxidative properties as well as other flavonoids 6 , 8 , 9 , 33 . Pinho-Ribeiro et al evaluated hesperidin in the rodent model to decrease inflammation-associated pain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hesperetin is known for its anti-inflammatory and antioxidative properties as well as other flavonoids 6 , 8 , 9 , 33 . Pinho-Ribeiro et al evaluated hesperidin in the rodent model to decrease inflammation-associated pain.…”
Section: Resultsmentioning
confidence: 99%
“…According to the results, hesperetin inhibited oxidative stress and inflammatory signals using down-regulation of critical cytokines in the inflammatory cascade, including TNF-, IL1ß, IL-6, and IL 10 35 , 36 . These interleukins and cytokines are widely involved in different inflammatory responses in the body, such as tooth and bone inflammation 6 , 9 . In the current study, human dental pulp stem cells were treated with both hesperetin and nano-hesperetin and inflamed by bacterial LPS and.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, developing new agents with the ability of anti-inflammatory, protect pulp stem cells and rapidly mobilize hDPSCs to promote the repairment of damaged pulp tissue, is still essential [ 20 ]. With the development of the material field, researchers have found that many biological materials can inhibit pulpitis and enhance the differentiation ability of hDPSCs, Such as baicalensis [ 21 ] and Curcumin [ 22 ] isolated from medicinal plant. In addition to this, many nanomaterials have also shown excellent anti-inflammatory ability, such as folic acid modified silver nanoparticles (FA-AgNPs) and [ 23 ]gold nanoparticles (AuNPs) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also previously been shown to have an antimicrobial activity following aPDT against both cariogenic planktonic cells 25 , 30 , 31 and, to a lesser degree, cariogenic biofilms 28 , 30 , 32 , 33 when applied as a solution. Furthermore, curcumin has been shown to either have no inhibitory effect 34 or promote cell viability 35 of dental pulp cells. While these earlier investigations have shown the significant potential of curcumin as a PS in aPDT in direct contact with the cells, the prevention and management of dental caries would significantly benefit from a more site-specific and sustained antimicrobial effect, particularly on critical tooth-restoration interfaces susceptible to recurrent caries.…”
Section: Introductionmentioning
confidence: 99%